27
Dec 22

## Final exam in Advanced Statistics ST2133, 2022

Unlike most UoL exams, here I tried to relate the theory to practical issues.

KBTU International School of Economics

Compiled by Kairat Mynbaev

The total for this exam is 41 points. You have two hours.

Everywhere provide detailed explanations. When answering please clearly indicate question numbers. You don’t need a calculator. As long as the formula you provide is correct, the numerical value does not matter.

Question 1. (12 points)

a) (2 points) At a casino, two players are playing on slot machines. Their payoffs $X,Y$ are standard normal and independent. Find the joint density of the payoffs.

b) (4 points) Two other players watch the first two players and start to argue what will be larger: the sum $U = X + Y$ or the difference $V = X - Y$. Find the joint density. Are variables $U,V$ independent? Find their marginal densities.

c) (2 points) Are $U,V$ normal? Why? What are their means and variances?

d) (2 points) Which probability is larger: $P(U > V)$ or $P\left( {U < V} \right)$?

e) (2 points) In this context interpret the conditional expectation $E\left( {U|V = v} \right)$. How much is it?

Reminder. The density of a normal variable $X \sim N\left( {\mu ,{\sigma ^2}} \right)$ is ${f_X}\left( x \right) = \frac{1}{{\sqrt {2\pi {\sigma ^2}} }}{e^{ - \frac{{{{\left( {x - \mu } \right)}^2}}}{{2{\sigma ^2}}}}}$.

Question 2. (9 points) The distribution of a call duration $X$ of one Kcell [largest mobile operator in KZ] customer is exponential: ${f_X}\left( x \right) = \lambda {e^{ - \lambda x}},\,\,x \ge 0,\,\,{f_X}\left( x \right) = 0,\,\,x < 0.$ The number $N$ of customers making calls simultaneously is distributed as Poisson: $P\left( {N = n} \right) = {e^{ - \mu }}\frac{{{\mu ^n}}}{{n!}},\,\,n = 0,1,2,...$ Thus the total call duration for all customers is ${S_N} = {X_1} + ... + {X_N}$ for $N \ge 1$. We put ${S_0} = 0$. Assume that customers make their decisions about calling independently.

a) (3 points) Find the general formula (when ${X_1},...,{X_n}$ are identically distributed and $X,N$ are independent but not necessarily exponential and Poisson, as above) for the moment generating function of $S_N$ explaining all steps.

b) (3 points) Find the moment generating functions of $X$, $N$ and ${S_N}$ for your particular distributions.

c) (3 points) Find the mean and variance of ${S_N}$. Based on the equations you obtained, can you suggest estimators of parameters $\lambda ,\mu$?

Remark. Direct observations on the exponential and Poisson distributions are not available. We have to infer their parameters by observing ${S_N}$. This explains the importance of the technique used in Question 2.

Question 3. (8 points)

a) (2 points) For a non-negative random variable $X$ prove the Markov inequality $P\left( {X > c} \right) \le \frac{1}{c}EX,\,\,\,c > 0.$

b) (2 points) Prove the Chebyshev inequality $P\left( {|X - EX| > c} \right) \le \frac{1}{c^2}Var\left( X \right)$ for an arbitrary random variable $X$.

c) (4 points) We say that the sequence of random variables $\left\{ X_n \right\}$ converges in probability to a random variable $X$ if $P\left( {|{X_n} - X| > \varepsilon } \right) \to 0$ as $n \to \infty$ for any $\varepsilon > 0$.  Suppose that $E{X_n} = \mu$ for all $n$ and that $Var\left(X_n \right) \to 0$ as $n \to \infty$. Prove that then $\left\{X_n\right\}$ converges in probability to $\mu$.

Remark. Question 3 leads to the simplest example of a law of large numbers: if $\left\{ X_n \right\}$ are i.i.d. with finite variance, then their sample mean converges to their population mean in probability.

Question 4. (8 points)

a) (4 points) Define a distribution function. Give its properties, with intuitive explanations.

b) (4 points) Is a sum of two distribution functions a distribution function? Is a product of two distribution functions a distribution function?

Remark. The answer for part a) is here and the one for part b) is based on it.

Question 5. (4 points) The Rakhat factory prepares prizes for kids for the upcoming New Year event. Each prize contains one type of chocolates and one type of candies. The chocolates and candies are chosen randomly from two production lines, the total number of items is always 10 and all selections are equally likely.

a) (2 points) What proportion of prepared prizes contains three or more chocolates?

b) (2 points) 100 prizes have been sent to an orphanage. What is the probability that 50 of those prizes contain no more than two chocolates?

22
Mar 22

## Blueprint for exam versions

This is the exam I administered in my class in Spring 2022. By replacing the Poisson distribution with other random variables the UoL examiners can obtain a large variety of versions with which to torture Advanced Statistics students. On the other hand, for the students the answers below can be a blueprint to fend off any assaults.

During the semester my students were encouraged to analyze and collect information in documents typed in Scientific Word or LyX. The exam was an open-book online assessment. Papers typed in Scientific Word or LyX were preferred and copying from previous analysis was welcomed. This policy would be my preference if I were to study a subject as complex as Advanced Statistics. The students were given just two hours on the assumption that they had done the preparations diligently. Below I give the model answers right after the questions.

## Midterm Spring 2022

You have to clearly state all required theoretical facts. Number all equations that you need to use in later calculations and reference them as necessary. Answer the questions in the order they are asked. When you don't know the answer, leave some space. For each unexplained fact I subtract one point. Put your name in the file name.

In questions 1-9 $X$ is the Poisson variable.

### Question 1

Define $X$ and derive the population mean and population variance of the sum $S_{n}=\sum_{i=1}^{n}X_{i}$ where $X_{i}$ is an i.i.d. sample from $X$.

Answer. $X$ is defined by $P\left( X=x\right) =e^{-\lambda }\frac{\lambda ^{x}}{x!},\ x=0,1,...$ Using $EX=\lambda$ and $Var\left( X\right) =\lambda$ (ST2133 p.80) we have

$ES_{n}=\sum EX_{i}=n\lambda ,$ $Var\left( S_{n}\right) =\sum V\left( X_{i}\right) =n\lambda$

(by independence and identical distribution). [Some students derived $EX=\lambda ,$ $Var\left( X\right) =\lambda$ instead of respective equations for sample means].

### Question 2

Derive the MGF of the standardized sample mean.

Answer. Knowing this derivation is a must because it is a combination of three important facts.

a) Let $z_{n}=\frac{\bar{X}-E\bar{X}}{\sigma \left( \bar{X}\right) }.$ Then $z_{n}=\frac{nS_{n}-EnS_{n}}{\sigma \left( nS_{n}\right) }=\frac{S_{n}-ES_{n} }{\sigma \left( S_{n}\right) },$ so standardizing $\bar{X}$ and $S_{n}$ gives the same result.

b) The MGF of $S_{n}$ is expressed through the MGF of $X$:

$M_{S_{n}}\left( t\right) =Ee^{S_{n}t}=Ee^{X_{1}t+...+X_{n}t}=Ee^{X_{1}t}...e^{X_{n}t}=$

(independence) $=Ee^{X_{1}t}...Ee^{X_{n}t}=$ (identical distribution) $=\left[ M_{X}\left( t\right) \right] ^{n}.$

c) If $X$ is a linear transformation of $Y,$ $X=a+bY,$ then

$M_{X}\left( t\right) =Ee^{X}=Ee^{\left( a+bY\right) t}=e^{at}Ee^{Y\left( bt\right) }=e^{at}M_{Y}\left( bt\right) .$

When answering the question we assume any i.i.d. sample from a population with mean $\mu$ and population variance $\sigma ^{2}$:

Putting in c) $a=-\frac{ES_{n}}{\sigma \left( S_{n}\right) },$ $b=\frac{1}{\sigma \left( S_{n}\right) }$ and using a) we get

$M_{z_{n}}\left( t\right) =E\exp \left( \frac{S_{n}-ES_{n}}{\sigma \left( S_{n}\right) }t\right) =e^{-ES_{n}t/\sigma \left( S_{n}\right) }M_{S_{n}}\left( t/\sigma \left( S_{n}\right) \right)$

(using b) and $ES_{n}=n\mu ,$ $Var\left( S_{n}\right) =n\sigma ^{2}$)

$=e^{-ES_{n}t/\sigma \left( S_{n}\right) }\left[ M_{X}\left( t/\sigma \left( S_{n}\right) \right) \right] ^{n}=e^{-n\mu t/\left( \sqrt{n}\sigma \right) }% \left[ M_{X}\left( t/\left( \sqrt{n}\sigma \right) \right) \right] ^{n}.$

This is a general result which for the Poisson distribution can be specified as follows. From ST2133, example 3.38 we know that $M_{X}\left( t\right)=\exp \left( \lambda \left( e^{t}-1\right) \right)$. Therefore, we obtain

$M_{z_{n}}\left( t\right) =e^{-\sqrt{\lambda }t}\left[ \exp \left( \lambda \left( e^{t/\left( n\sqrt{\lambda }\right) }-1\right) \right) \right] ^{n}= e^{-t\sqrt{\lambda }+n\lambda \left( e^{t/\left( n\sqrt{\lambda }\right) }-1\right) }.$

[Instead of $M_{z_n}$ some students gave $M_X$.]

### Question 3

Derive the cumulant generating function of the standardized sample mean.

Answer. Again, there are a couple of useful general facts.

I) Decomposition of MGF around zero. The series $e^{x}=\sum_{i=0}^{\infty } \frac{x^{i}}{i!}$ leads to

$M_{X}\left( t\right) =Ee^{tX}=E\left( \sum_{i=0}^{\infty }\frac{t^{i}X^{i}}{ i!}\right) =\sum_{i=0}^{\infty }\frac{t^{i}}{i!}E\left( X^{i}\right) =\sum_{i=0}^{\infty }\frac{t^{i}}{i!}\mu _{i}$

where $\mu _{i}=E\left( X^{i}\right)$ are moments of $X$ and $\mu _{0}=EX^{0}=1.$ Differentiating this equation yields

$M_{X}^{(k)}\left( t\right) =\sum_{i=k}^{\infty }\frac{t^{i-k}}{\left( i-k\right) !}\mu _{i}$

and setting $t=0$ gives the rule for finding moments from MGF: $\mu _{k}=M_{X}^{(k)}\left( 0\right) .$

II) Decomposition of the cumulant generating function around zero. $K_{X}\left( t\right) =\log M_{X}\left( t\right)$ can also be decomposed into its Taylor series:

$K_{X}\left( t\right) =\sum_{i=0}^{\infty }\frac{t^{i}}{i!}\kappa _{i}$

where the coefficients $\kappa _{i}$ are called cumulants and can be found using $\kappa _{k}=K_{X}^{(k)}\left( 0\right)$. Since

$K_{X}^{\prime }\left( t\right) =\frac{M_{X}^{\prime }\left( t\right) }{ M_{X}\left( t\right) }$ and $K_{X}^{\prime \prime }\left( t\right) =\frac{ M_{X}^{\prime \prime }\left( t\right) M_{X}\left( t\right) -\left( M_{X}^{\prime }\left( t\right) \right) ^{2}}{M_{X}^{2}\left( t\right) }$

we have

$\kappa _{0}=\log M_{X}\left( 0\right) =0,$ $\kappa _{1}=\frac{M_{X}^{\prime }\left( 0\right) }{M_{X}\left( 0\right) }=\mu _{1},$

$\kappa _{2}=\mu _{2}-\mu _{1}^{2}=EX^{2}-\left( EX\right) ^{2}=Var\left( X\right) .$

Thus, for any random variable $X$ with mean $\mu$ and variance $\sigma ^{2}$ we have

$K_{X}\left( t\right) =\mu t+\frac{\sigma ^{2}t^{2}}{2}+$ terms of higher order for $t$ small.

III) If $X=a+bY$ then by c)

$K_{X}\left( t\right) =K_{a+bY}\left( t\right) =\log \left[ e^{at}M_{Y}\left( bt\right) \right] =at+K_{X}\left( bt\right) .$

IV) By b)

$K_{S_{n}}\left( t\right) =\log \left[ M_{X}\left( t\right) \right] ^{n}=nK_{X}\left( t\right) .$

Using III), $z_{n}=\frac{S_{n}-ES_{n}}{\sigma \left( S_{n}\right) }$ and then IV) we have

$K_{z_{n}}\left( t\right) =\frac{-ES_{n}}{\sigma \left( S_{n}\right) } t+K_{S_{n}}\left( \frac{t}{\sigma \left( S_{n}\right) }\right) =\frac{-ES_{n} }{\sigma \left( S_{n}\right) }t+nK_{X}\left( \frac{t}{\sigma \left( S_{n}\right) }\right) .$

For the last term on the right we use the approximation around zero from II):

$K_{z_{n}}\left( t\right) =\frac{-ES_{n}}{\sigma \left( S_{n}\right) } t+nK_{X}\left( \frac{t}{\sigma \left( S_{n}\right) }\right) \approx \frac{ -ES_{n}}{\sigma \left( S_{n}\right) }t+n\mu \frac{t}{\sigma \left( S_{n}\right) }+n\frac{\sigma ^{2}}{2}\left( \frac{t}{\sigma \left( S_{n}\right) }\right) ^{2}$

$=-\frac{n\mu }{\sqrt{n}\sigma }t+n\mu \frac{t}{\sqrt{n}\sigma }+n\frac{ \sigma ^{2}}{2}\left( \frac{t}{\sigma \left( S_{n}\right) }\right) ^{2}=t^{2}/2.$

[Important. Why the above steps are necessary? Passing from the series $M_{X}\left( t\right) =\sum_{i=0}^{\infty }\frac{t^{i}}{i!}\mu _{i}$ to the series for $K_{X}\left( t\right) =\log M_{X}\left( t\right)$ is not straightforward and can easily lead to errors. It is not advisable in case of the Poisson to derive $K_{z_{n}}$ from $M_{z_{n}}\left( t\right) =$ $e^{-t \sqrt{\lambda }+n\lambda \left( e^{t/\left( n\sqrt{\lambda }\right) }-1\right) }$.]

### Question 4

Prove the central limit theorem using the cumulant generating function you obtained.

Answer. In the previous question we proved that around zero

$K_{z_{n}}\left( t\right) \rightarrow \frac{t^{2}}{2}.$

This implies that

(1) $M_{z_{n}}\left( t\right) \rightarrow e^{t^{2}/2}$ for each $t$ around zero.

But we know that for a standard normal $X$ its MGF is $M_{X}\left( t\right) =\exp \left( \mu t+\frac{\sigma ^{2}t^{2}}{2}\right)$ (ST2133 example 3.42) and hence for the standard normal

(2) $M_{z}\left( t\right) =e^{t^{2}/2}.$

Theorem (link between pointwise convergence of MGFs of $\left\{ X_{n}\right\}$ and convergence in distribution of $\left\{ X_{n}\right\}$) Let $\left\{ X_{n}\right\}$ be a sequence of random variables and let $X$ be some random variable. If $M_{X_{n}}\left( t\right)$ converges for each $t$ from a neighborhood of zero to $M_{X}\left( t\right)$, then $X_{n}$ converges in distribution to $X.$

Using (1), (2) and this theorem we finish the proof that $z_{n}$ converges in distribution to the standard normal, which is the central limit theorem.

### Question 5

State the factorization theorem and apply it to show that $U=\sum_{i=1}^{n}X_{i}$ is a sufficient statistic.

Answer. The solution is given on p.180 of ST2134. For $x_{i}=1,...,n$ the joint density is

(3) $f_{X}\left( x,\lambda \right) =\prod\limits_{i=1}^{n}e^{-\lambda } \frac{\lambda ^{x_{i}}}{x_{i}!}=\frac{\lambda ^{\Sigma x_{i}}e^{-n\lambda }}{\Pi _{i=1}^{n}x_{i}!}.$

To satisfy the Fisher-Neyman factorization theorem set

$g\left( \sum x_{i},\lambda \right) =\lambda ^{\Sigma x_{i}e^{-n\lambda }},\ h\left( x\right) =\frac{1}{\Pi _{i=1}^{n}x_{i}!}$

and then we see that $\sum x_{i}$ is a sufficient statistic for $\lambda .$

### Question 6

Find a minimal sufficient statistic for $\lambda$ stating all necessary theoretical facts.

AnswerCharacterization of minimal sufficiency A statistic $T\left( X\right)$ is minimal sufficient if and only if level sets of $T$ coincide with sets on which the ratio $f_{X}\left( x,\theta \right) /f_{X}\left( y,\theta \right)$ does not depend on $\theta .$

From (3)

$f_{X}\left( x,\lambda \right) /f_{X}\left( y,\lambda \right) =\frac{\lambda ^{\Sigma x_{i}}e^{-n\lambda }}{\Pi _{i=1}^{n}x_{i}!}\left[ \frac{\lambda ^{\Sigma y_{i}}e^{-n\lambda }}{\Pi _{i=1}^{n}y_{i}!}\right] ^{-1}=\lambda ^{ \left[ \Sigma x_{i}-\Sigma y_{i}\right] }\frac{\Pi _{i=1}^{n}y_{i}!}{\Pi _{i=1}^{n}x_{i}!}.$

The expression on the right does not depend on $\lambda$ if and only of $\Sigma x_{i}=\Sigma y_{i}0.$ The last condition describes level sets of $T\left( X\right) =\sum X_{i}.$ Thus it is minimal sufficient.

### Question 7

Find the Method of Moments estimator of the population mean.

Answer. The idea of the method is to take some populational property (for example, $EX=\lambda$) and replace the population characteristic (in this case $EX$) by its sample analog ($\bar{X}$) to obtain a MM estimator. In our case $\hat{\lambda}_{MM}= \bar{X}.$ [Try to do this for the Gamma distribution].

### Question 8

Find the Fisher information.

Answer. From Problem 5 the log-likelihood is

$l_{X}\left( \lambda ,x\right) =-n\lambda +\sum x_{i}\log \lambda -\sum \log \left( x_{i}!\right) .$

Hence the score function is (see Example 2.30 in ST2134)

$s_{X}\left( \lambda ,x\right) =\frac{\partial }{\partial \lambda } l_{X}\left( \lambda ,x\right) =-n+\frac{1}{\lambda }\sum x_{i}.$

Then

$\frac{\partial ^{2}}{\partial \lambda ^{2}}l_{X}\left( \lambda ,x\right) =- \frac{1}{\lambda ^{2}}\sum x_{i}$

and the Fisher information is

$I_{X}\left( \lambda \right) =-E\left( \frac{\partial ^{2}}{\partial \lambda ^{2}}l_{X}\left( \lambda ,x\right) \right) =\frac{1}{\lambda ^{2}}E\sum X_{i}=\frac{n\lambda }{\lambda ^{2}}=\frac{n}{\lambda }.$

### Question 9

Derive the Cramer-Rao lower bound for $V\left( \bar{X}\right)$ for a random sample.

Answer. (See Example 3.17 in ST2134) Since $\bar{X}$ is an unbiased estimator of $\lambda$ by Problem 1, from the Cramer-Rao theorem we know that

$V\left( \bar{X}\right) \geq \frac{1}{I_{X}\left( \lambda \right) }=\frac{ \lambda }{n}$

and in fact by Problem 1 this lower bound is attained.